Screening and characterization of fibrolytic bacteria from sago waste - Mohd Almuhsen, Karim (Universiti Malaysia Sarawak (UNIMAS), 2012)
A total of 16 bacteria were successfully isolated from the sago waste after selectively enriched in media containing 1 % (w/v) of corn cobs. Screening of the bacterial isolates was done by using Congo-red staining method after the bacterial strains was cultured onto the CMC agar plates and 1 % corn cobs agar plates, respectively. Four isolates were chosen and selected for further analysis due to their ability to produce large halo and characterized. Standard biochemical test, morphological characterization, cellulase enzyme assay, xylanase enzyme assay and molecular characterization were done on these four isolates. Enzyme assays were conducted using ONS method. After ONA sequencing with 16s rONA analysis, the isolates were found to be similar to Bacillus pumilus and Bacillus subtiUs.